The Effect of Manhole Form on Double Bottom Ship Construction - Rudianto; Ede Mehta Wardhana; Jangka Rulianto; R Puranggo Ganjar Widityo; Ansori (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The ship's hull construction must withstand all loads, be made as light as possible and comply with regulations. The purpose of this study was to determine the maximum strength limit of double bottom ship construction with manhole form variations. Research design for this study; literature studies, field studies, and simulations using ANSYS. The results of the existing double model structure strength values for the maximum stress values in the sagging hogging state are 236.60 MPa and 154.18 MPa. Von Mises stress values are 227.94 MPa and 136.26 MPa. The shear stress values are 131.5 MPa and 77.36 MPa. The maximum deformation is 0.0049 m, and the safety factor is 1.346. The total construction weight is 201.83 metric tons. The best results of the analysis of variation were found in Model B1, which changed the hole ratio from 0.75 to 0.6 and increased the hole dimension by 200 mm. The maximum stress values of Model B1 in the sagging-hogging condition are 186.93 MPa and 141.54 MPa. Von Mises stress values are 238.72 MPa and 184.82 MPa. The shear stress values are 113.37 MPa and 137.42 MPa. The safety factor is 1.337 m, and the maximum deformation is 0.0034 m.